Diagnosis and Treatment of Synchronous Lymphoma and Digestive System Carcinoma: Report of Four Cases and Literature Review - Meng, Jingshu; Pan, Huaxiong; Li, Xiaoqian; Liu, Tao; Liu, Zijian; Li, Qiuhui; Xiao, Yin; Liu, Xinxiu; Wu, Gang; Zhu, Fang; Zhang, Liling (Frontiers in Oncology, 2019)
Objective: To investigate the diagnosis and treatment of synchronous lymphoma and digestive system carcinoma and review literature. Materials and Methods: We retrospectively analyzed the clinical data of 4 cases of synchronous lymphoma and digestive system carcinoma treated at our hospital. The clinical manifestations, pathological results, and treatment strategies were investigated. Results: One of the 4 cases was diagnosed as follicular lymphoma with gastric adenocarcinoma, and the other three were diagnosed as diffuse large B cell lymphoma with digestive system adenocarcinoma in the liver, sigmoid colon and duodenum papilla, respectively. The second carcinoma was initially discovered incidentally because of the stage examination of lymphoma or the patients’ poor response to treatment. The diagnosis of synchronous lymphoma and digestive system carcinoma depended mainly on the pathological examination. Conclusions: The accurate diagnosis of synchronous malignancies is challenging since they rarely occur. We suggest a scrupulous re-biopsy of extranodal lesions in patients with lymphoma to improve the diagnostic accuracy of related double primary tumors. Age, performance status, symptoms, pathological types, and tumor staging should be considered when formulating a treatment strategy. The systemic treatment regimens should include drugs targeting the synchronous tumors in question, and these remain to be explored further.